Standing in another man's grave [large type] - Rankin, Ian (Rankin, Ian. Inspector Rebus novel series., 2013)
For the last decade, Nina Hazlitt has been ready to hear the worst about her daughter's disappearance. But the police investigation ground to a halt long ago, and Nina's pleas to the cold case department have led her nowhere. Then she meets the newest member of the team: former detective John Rebus, who has never shied away from lost causes. Two more women have gone missing from the same road, and he can sense a connection.